Comparing the effects of dietary selenium and mannan oligosaccharide supplementation on the growth, immune function, and antioxidant enzyme activity in the cultured marron Cherax cainii (Austin, 2002) - Nugroho, Rudy; Fotedar, Ravi (Springer-Verlag Dordrecht, 2013)
This study was conducted to compare the effects of dietary supplementation of selenium (Se, both inorganic and organic) and mannan oligosaccharide (MOS) on the growth, immune function, and antioxidant enzyme activities in the haemolymph of the marron Cherax cainii (Austin, 2002); 0.4 mg kg-1 of sodium selenate, 0.2 g kg-1 Sel-Plex®, or 0.4 % Bio-MOS® was added to the basal diet as sources of inorganic selenium (IS), organic selenium (OS), and MOS, respectively. After 90 days, marron fed all 3 supplemented test diets had significantly higher final weight, specific growth rate (SGR), survival, total haemocyte count (THC), percentage of hyaline cells, glutathione-S-transferase (GST), and glutathione peroxidase (GPx) activities than marron fed without any supplements. The marron fed OS showed significantly higher THC and percentage of hyaline cells than those fed IS and MOS. Marron fed MOS showed the highest final weight, SGR, and percentage of granular cells; however, there was no significant difference in the neutral red time retention between marron fed IS and OS, whereas marron fed OS resulted in the highest GPx activity and total Se levels in the haemolymph but the lowest lipid peroxidase activity; therefore, it is suggested that dietary supplementation with any source of Se and MOS is beneficial to improving growth, survival, and antioxidant activity.